2004
DOI: 10.1128/jvi.78.13.7079-7088.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antisense-Mediated Inhibition of Human Immunodeficiency Virus (HIV) Replication by Use of an HIV Type 1-Based Vector Results in Severely Attenuated Mutants Incapable of Developing Resistance

Abstract: We have constructed a human immunodeficiency virus type 1 (HIV-1)-based lentiviral vector expressing a 937-base antisense sequence against the HIV-1 envelope gene. Transduction of CD4 ؉ T lymphocytes with this vector results in expression of the therapeutic antisense sequence and subsequent inhibition of productive HIV-1 replication. In this report, we examined the effect of antisense-mediated suppression on the potential development of virus escape mutants using a permissive T-cell line cultured under conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 46 publications
(39 reference statements)
5
78
0
Order By: Relevance
“…This LTR-dependent transcriptional upregulation is in contrast to self-inactivating vectors, where the LTRs are modified by deletion of the U3 region, and transgene expression is driven from a heterologous internal promoter. An advantage of using a long antisense sequence is that it targets multiple sites of HIV genomic RNA, constraining the pathogenic virus' ability to form resistance mutants without adversely affecting viral fitness (2). In preclinical studies bringing these two technologies together, the rationale for the present clinical study was supported by the potent antiviral effects that were demonstrated in vitro, regardless of patient status or the tropism of the infecting virus (5).…”
Section: Lentiviral Vectors Appear Promising For Gene Transfer To Hummentioning
confidence: 64%
See 1 more Smart Citation
“…This LTR-dependent transcriptional upregulation is in contrast to self-inactivating vectors, where the LTRs are modified by deletion of the U3 region, and transgene expression is driven from a heterologous internal promoter. An advantage of using a long antisense sequence is that it targets multiple sites of HIV genomic RNA, constraining the pathogenic virus' ability to form resistance mutants without adversely affecting viral fitness (2). In preclinical studies bringing these two technologies together, the rationale for the present clinical study was supported by the potent antiviral effects that were demonstrated in vitro, regardless of patient status or the tropism of the infecting virus (5).…”
Section: Lentiviral Vectors Appear Promising For Gene Transfer To Hummentioning
confidence: 64%
“…clinical trials ͉ HIV ͉ immunotherapy ͉ gene therapy I n preclinical studies, a highly efficient T cell culture system and a lentiviral vector containing a long antisense sequence to HIV envelope were developed (1)(2)(3). In a prior phase I trial, autologous CD4 cells from HIV-infected subjects were expanded ex vivo by using anti-CD3͞CD28 beads as artificial antigen presenting cells, and adoptive transfer of the activated CD4 ϩ T cells was shown to result in dose-dependent increases in the steady-state CD4 ϩ T cell counts by induction of resident CD4 ϩ cell proliferation and a sustained decrease in CCR5 expression in vivo (4).…”
Section: Lentiviral Vectors Appear Promising For Gene Transfer To Hummentioning
confidence: 99%
“…Antisense RNAs are short or long single-stranded RNA molecules binding to complementary HIV-1 mRNAs resulting in the formation of non-functional duplexes. Antisense molecules directed against the HIV-1 trans-activation response element (TAR) and the viral envelope RNA have been developed (Humeau et al, 2004;Lu et al, 2004;Vickers et al, 1991). The conditionally replicating lentiviral vector VRX496 TM encodes a long antisense gene against the HIV-1 envelope.…”
Section: Antiviral Rnasmentioning
confidence: 99%
“…More recently, a clinical trial using an HIV LTR-expressed anti-env antisense has been reported 9 . Although the actual mechanism by which these antisense transcripts inhibit HIV replication is not clear, it may involve triggering extensive adenosine deamination of the HIV-antisense duplex, resulting in nuclear retention of transcripts or the generation of multiple viral-disabling mutations 10 .…”
mentioning
confidence: 99%